A new species of the genus Thoracibidion Martins, 1960 from Mexico (Coleoptera: Cerambycidae: Cerambycinae: Tropidini: Tropidina) - Noguera, Felipe A. (Zootaxa, 2025)
Thoracibidion mariavanessae sp. nov. is described from western Mexico. Individuals of this species were collected in the temperate forests of the Nevado de Colima and represent the northernmost record of this genus, which has its greatest diversity in South America.